Learning styles towards mathematics achievements among higher education students - Ahmad, Sabri; Safee, Shuhaili; Wan Afthanorhan, Wan Mohamad Asyraf (Global Journal of Mathematical Analysis, 2014)
Students all have unique learning styles and preferences. Some may like group instruction while others may enjoy individualized instruction. Some learners are more independent than other learners. The aim of the present study was to identify the learning styles towards mathematic achievements among higher education students. One hundred and fifty-three first year students in a mathematic course participated in the study. Grasha-Riehmann Learning Style Scale was used to determine students’ learning styles. Grasha-Riehmann Learning Style Scale consists of six learning style (independent, dependent, avoidant, and participant, collaborative and competitive). By used cluster analysis, 4 cluster/groups are obtained. As cluster 1 is identified as collaborative and competitive, cluster 2 is collaborative, dependent and participant, cluster 3 competitive and cluster 4 is collaborative. Results based on ANOVA test shown that, there was no significant among students with different learning styles with respect to mathematic achievement. Keywords: Cluster Analysis, Anova, Grasha-Riehmann Learning Style.